Occupational Safety and Health Vulnerability among Brick Factory Workers in Dhading District, Nepal - Dinesh Rupakheti (Ubiquity Press, 2018)
Background: Occupational safety and health vulnerability considers multiple dimensions, such as hazard, policy/procedure to protect workers, workers’ awareness and their empowerment to participate in injury prevention. This study attempts to bridge the inadequate knowledge regarding the factors associated with occupational safety and health vulnerability in brick factories. Objectives: To identify the status and factors associated with occupational safety and health vulnerability among brick factory workers in Dhading district. Methods: A cross-sectional descriptive study was carried out in five brick kilns of Dhading district. A two-stage cluster sampling method was used; at the first stage, probability proportionate to sample size was used to select the brick factories and simple random sampling was used to select participants from each selected brick factory. A total of 201 workers with at least a year of experience and who had worked over the last year in brick factories were included in the study. The data was collected through face-to-face interviews using a structured questionnaire. Vulnerability was defined as exposed to hazards and having inadequate policies, procedures, awareness and empowerment. Pearson Chi-square test was used to examine the relationship between vulnerability and demographic, occupational and workplace characteristics. Results: Four-fifths of the participants experienced occupational safety and health vulnerability. All participants experienced policy/procedure vulnerability; four-fifths experienced hazard vulnerability and about two-thirds experienced awareness and empowerment vulnerability. Younger, nonnative immigrants, workers carrying bricks out of a chimney and workers from small-sized workplaces experienced higher odds of vulnerability across all domains and overall vulnerability. Conclusion: Occupational safety and health vulnerability was very high among the brick factory workers. Young workers, non-native immigrant workers, workers carrying cooked bricks out of a chimney and workers from small-sized workplace were found to be more vulnerable.